Tillage and mulching options for conserving soil and water and improving livelihoods in foothills of lower Shiwaliks - BHATT, RAJAN; ARORA, SANJAY (Journal of Soil and Water Conservation, 2019)
The foothill of lower Shiwaliks is a submontaneous tract of north-western Himalaya that is prone to soil erosion by water. Soils of the area are coarse in texture, low in organic matter and poor in fertility. High intensity rains during the monsoon season result in fertile topsoil removal. Foothill regions have steep slopes, sandy soil and scanty vegetation cover along with intense rainfalls. Climate change further accelerated the process. To avert continued land degradation, soil productivity balance must be shifted to conservation practices. Soil erosion have their origin in social, economic and cultural factors that translate into the over-exploitation of the natural resources and the application of inadequate practices for the management of soils and water. Among different combinations of tillage and mulching, zero/ minimum tillage with mulch on whole area at a rate of 6-8 t ha-1 found to be the best in reducing the soil erosion by improving different soil properties thereby finally improving the livelihoods of the foothill farmers. There is need to adopt effective tillage and mulching options for conserving soil and water and improving livelihoods in foothills of lower Shiwaliks.